2018
DOI: 10.1103/physrevlett.120.031104
|View full text |Cite
|
Sign up to set email alerts
|

First Search for Nontensorial Gravitational Waves from Known Pulsars

Abstract: We present results from the first directed search for nontensorial gravitational waves. While general relativity allows for tensorial (plus and cross) modes only, a generic metric theory may, in principle, predict waves with up to six different polarizations. This analysis is sensitive to continuous signals of scalar, vector, or tensor polarizations, and does not rely on any specific theory of gravity. After searching data from the first observation run of the advanced LIGO detectors for signals at twice the r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
59
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(61 citation statements)
references
References 50 publications
0
59
0
2
Order By: Relevance
“…In fact, GW170814 was the first GW event to test the polarization content of GWs. The analysis revealed that the pure tensor polarizations are favored against pure vector and pure scalar polarizations [4,15]. With the advent of more advanced detectors, there exists a better chance to pin down the polarization content and thus, the nature of gravity in the near future.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, GW170814 was the first GW event to test the polarization content of GWs. The analysis revealed that the pure tensor polarizations are favored against pure vector and pure scalar polarizations [4,15]. With the advent of more advanced detectors, there exists a better chance to pin down the polarization content and thus, the nature of gravity in the near future.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1 shows the sky map, which is the contour map for the coefficients of the scalar modes in the null streams by Eqs. (9) and (10). At some positions in the contour map, one can recognize an octapolar behavior of some curves.…”
Section: Suppression Of Spin-0 Modesmentioning
confidence: 96%
“…Therefore, let us examine how often the simultaneous suppression of the four vector coefficients in Eqs. (9) and (10) can occur.…”
Section: Suppression Of Spin-1 Modesmentioning
confidence: 99%
See 2 more Smart Citations